2014
DOI: 10.4103/0973-1075.138400
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care needs of Iranian cancer patients

Abstract: Background:A supportive needs assessment is an essential component of any care program. There is no research evidence regarding the supportive care needs of cancer patients in Iran or other Middle Eastern countries.Aims:The aim of this study was to determine the supportive care needs of Iranian cancer patients.Materials and Methods:This descriptive study was conducted in a referral medical center in the northwest of Iran. A total of 274 cancer patients completed the Supportive Care Needs Survey (SCNS-59). Desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 35 publications
6
41
0
6
Order By: Relevance
“…21 The aim of this article was to access factors which predict Iranian cancer patients unmet supportive care needs.…”
Section: Discussionmentioning
confidence: 99%
“…21 The aim of this article was to access factors which predict Iranian cancer patients unmet supportive care needs.…”
Section: Discussionmentioning
confidence: 99%
“…Using a range of 1.00–5.00, many of these studies recorded mean values close to or more than the average for the health system and information domain [1,8,10,25-28]. The consistency of this finding across different types of cancers and varying locations in Malaysia, Singapore [29], South Korea [30], Hong Kong [31], Australia [27], Europe, United States [26], Canada [18], and the United Kingdom further establishes the importance of the health system and information domain.…”
Section: Reviewmentioning
confidence: 99%
“…Similar finding have been reported by others. In a study conducted in Iran it is reported that cancer patients have many unmet supportive care needs, especially in the domains of health system, information, physical and daily livings where more than half of the participants reported unmet supportive care needs (Rahmani, et al, 2014). Similar finding was reported by Michael, et al (2013).…”
Section: Palliative Care Needs and The Care Received By Adult Cancer supporting
confidence: 72%